CHECKLIST OF SPIDER FAUNA (ARACHNIDA: ARANEAE) IN THE BANANA FIELDS OF DISTRICT MATIARI, SINDH, PAKISTAN (The Research of Medical Science Review, 2025)
There is an contiguous requisite to investigate Pakistan's spider fauna, documented and conserve spiders due to their diverse predatory efficiencies and great medical importance. Role in formation of food web also participation in IPM, the current study focused on exploring new habitats of this valuable arthropods and the to give the checklist. The Banana is the major cash crop of Pakistan particularly from Sindh Province. District Matiari is famous for banana fields. About 80% banana production contributed by Sindh province and from Sindh about 40% banana produced by District Matiari. Consequently, the current research is focused on the spider fauna above mentioned site with the aim of distinguishing and developing a checklist of spiders. Diversity of spiders fauna was measured very rich in the District Matiari; due to its favorite climatic and abiotic (temperature and humidity) conditions.for the collection of spiders specimens banana fields were selected, surveyed during 2021- 2022. The findings showed that 992 specimens were collected, which sorted out into 13 species, and 09 genera and 6 families.